Association Between ABCB1 Polymorphism and Stable Warfarin Dose Requirements in Brazilian Patients - Tavares, Letícia C.; Marcatto, Leiliane R.; Soares, Renata A. G.; Krieger, Jose E.; Pereira, Alexandre C.; Santos, Paulo C. J. L. (Frontiers in Pharmacology, 2018)
The ideal dose of the oral anticoagulant warfarin varies widely among patients, mainly due to genetic factors. Genetic variations that impact warfarin pharmacokinetics and the vitamin K cycle are plausible candidates for being associated with warfarin dose requirements. Therefore, the aim of this study was to assess whether polymorphisms in the ABCB1 and CYP4F2 genes were associated with stable warfarin dose requirements in Brazilian patients. This retrospective study included samples from 309 individuals. Genotyping of ABCB1 c.3435C>T and CYP4F2 c.1297G>A were performed by polymerase chain reaction followed by melting curve analysis (HRM-PCR) and TaqMan® genotyping assay, respectively. Stable doses were adjusted in a linear multiple regression model for age, gender, body mass index, self-reported race, use of amiodarone, CYP2C9 (*2 and *3), VKORC1 c.1639G>A, and ABCB1 c.3435C>T or CYP4F2 c.1297G>A. By performing a univariate analysis of variance, we found that the warfarin patients who carry ABCB1 c.3435T variant alleles (CT and TT genotypes) need fewer warfarin stable doses in comparison with the individuals that are CC wild-type: 2.5 (p=0.003) and 4.3 (p<0.001) mg/week less, respectively, for the overall group of patients on stable anticoagulation therapeutics (n=309); and 5.5 (p=0.006) and 10.2 (p<0.001) mg/week less, respectively, for the self-declared non-white stable subgroup (n=76). No statistically significant differences in dose requirements were observed according to CYP4F2 genotypes. In conclusion, our results suggest ABCB1 c.3435C>T variant may influence warfarin dose requirements in Brazilian patients, when associated with other genotypic, demographic and clinical factors.